Panel data and structural labour market models - Bunzel, H. (Contributions to economic analysis ;, 2000)
Panel Data and Structural Labour Market Models is the latest volume in a series of four, reporting on the original work of an international group of scholars with research interests in the performance of the labour markets that condition the dynamic labour market experiences of individual workers. The book contains papers focusing on theoretical and empirical modelling of the labour market covering both wage equilibrium models and models for labour market transition. Contributions range from the theoretical or econometric through empirical structural methods and exploratory data analysis based on employer and employee level data. Academic libraries, labour economists, labour and industrial relations research institutes and statistical agencies will find this a particularly useful piece of work.